Club Cell Loss as a Feature of Bronchiolization in ILD - Reynaud, Paul; Ahmed, Engi; Serre, Isabelle; Knabe, Lucie; Bommart, Sébastien; Suehs, Carey; Vachier, Isabelle; Berthet, Jean Philippe; Romagnoli, Micaela; Vernisse, Charlotte; Mallet, Jean Pierre; Gamez, Anne Sophie; et al. (Frontiers in Immunology, 2021)
Background Distal airway metaplasia may precede honeycombing in progressive-fibrosing interstitial lung disease (ILD). The SCGB1A1+ve bronchiolar-specific Club cells may play a role in this aberrant regenerative process. objective To assess the presence of Club cells in the small airways of patients suffering of ILD. Methods Small airways (Pi <2mm) in lung samples (surgical lung biopsy (SLB) and/or transbronchial lung cryobiopsy (TBLC)) from 14 patients suffering from ILD and 10 controls were morphologically assessed and stained for SCGB1A1. SCGB1A1 was weighted by epithelial height as a marker of airway generation (SCGB1A1/EH). Correlations between clinical, functional and high resolution computed tomography (HRCT) prognostic factors and histomorphometry were assessed. Results ILD and control samples significantly differed in density of SCGB1A1+ve cells in their small airways (0.064 [0.020-0.172] vs 0.393 [0.082-0.698], p<.0001). UIP patterns most frequently contained small airways with limited or absence of SCGB1A1 expression (SCGB1A1/EH < 0.025): UIP (17/30; 57%) as compared with non-UIP patterns (5/34; 15%) or controls (0/34; 0%): p<0.0001. In addition, correlations with HRCT indicated significant negative relationship between SCGB1A1 and bronchiectasis as a feature of bronchiolization (Rho -0.63, p<.001) and a positive relationship with both FVC and HU-distribution pattern Kurtosis (Rho 0.38 and 0.50 respectively, both p<.001) as markers of fibrotic changes. Conclusion Compared with controls, small airways of patients with ILD more often lack SCGB1A1 and especially so in UIP. Low densities of SCGB1A1-marked cells correlates with bronchiectasis and fibrotic changes. SCGB1A1 staining may be considered as a pathological feature of the bronchiolization process.